2003
DOI: 10.1038/sj.cdd.4401314
|View full text |Cite
|
Sign up to set email alerts
|

Role of N-terminal tau domain integrity on the survival of cerebellar granule neurons

Abstract: Although the role of the microtubule-binding domain of the tau protein in the modulation of microtubule assembly is widely established, other possible functions of this protein have been poorly investigated. We have analyzed the effect of adenovirally mediated expression of two fragments of the Nterminal portion -free of microtubule-binding domain -of the tau protein in cerebellar granule neurons (CGNs). We found that while the expression of the tau (1-230) fragment, as well as of full-length tau, inhibits the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 64 publications
(65 reference statements)
4
59
0
Order By: Relevance
“…In our previous study, we observed that moderate overexpression of full-length htau in cerebellar granule cells (CGCs), although protective against K ϩ deprivation-induced cell death, caused a rapid Ϸ20% cell death, and we surmised that it would be attributed to the high level of tau expression reached in some neurons (18). To test our hypothesis we infected CGCs at 4 days in vitro with various multiplicities of infection (MOIs) of tau-(1-441) vector and Lac-Z vector as control and assayed for neuronal death 24 and 48 h later.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we observed that moderate overexpression of full-length htau in cerebellar granule cells (CGCs), although protective against K ϩ deprivation-induced cell death, caused a rapid Ϸ20% cell death, and we surmised that it would be attributed to the high level of tau expression reached in some neurons (18). To test our hypothesis we infected CGCs at 4 days in vitro with various multiplicities of infection (MOIs) of tau-(1-441) vector and Lac-Z vector as control and assayed for neuronal death 24 and 48 h later.…”
Section: Resultsmentioning
confidence: 99%
“…Viable CGCs and cortical neurons were quantified by the MTT tetrazolium salt assay, by counting the number of intact nuclei (18), or by counting the number of condensed nuclei after Hoechst 33342 staining.…”
Section: Infection Of Neuronsmentioning
confidence: 99%
“…However, it is very difficult to show that such a mechanism can (and more importantly [108,109,138,139,213,214].…”
Section: Is Tau a Prion?mentioning
confidence: 99%
“…34 Furthermore, if one of such truncated tau forms was introduced into the same healthy neurons by adenovirusmediated transduction, it evoked a massive and rapid cell death 35 involving extrasynaptic NR2B-subunit-containing NMDARs, dephosphorylation of cAMP-response-elementbinding protein, sustained and delayed activation of extracellular-regulated kinases 1/2 and calpain-I. 36 In addition, the pro-apoptotic shifting to a low potassium medium induced a marked failure of mitochondrial oxidative phosphorylation, accompanied by a dramatic intracellular ATP drop and by an increased production of reactive oxidative species.…”
Section: Amyloidogenesis and Apoptosismentioning
confidence: 99%